Helix pomatia – Withdrawal and Restlessness - Göckenjan-Storz, Irmela (Homœopathic Links, 2012)
This article is to illustrate the medicinal relevance of edible snails by focussing on one case and condensing the experience of another ten that were successfully treated.
Keywords: Helix pomatia; Roman snail; Mollusca; Animal kingdom; Sensation method; Manic depression